Individual-based modeling for biofilm structure control - Li, Cheng (2017)
Biofilm growth is affected by many factors such as substratum surface properties, fluidic conditions, and medium supply. In this thesis, we investigated biofilm structure development by considering the influence of three key factors: biofilm detachment, oxygen availability, and calcium concentration. This thesis mainly focused on the mathematical modeling of biofilms. Biofilm experiments were also conducted to validate the results of mathematical models.